Gpr174 Knockout Alleviates DSS-Induced Colitis via Regulating the Immune Function of Dendritic Cells - Wei, Wei; Mu, Sucheng; Han, Yi; Chen, Yao; Kuang, Zhongshu; Wu, Xingyue; Luo, Yue; Tong, Chaoyang; Zhang, Yiqun; Yang, Yilin; Song, Zhenju (Frontiers in Immunology, 2022)
Background Dysfunction of the immune system would disturb the intestinal homeostasis and lead to inflammatory bowel disease (IBD). Dendritic cells (DCs) help maintain intestinal homeostasis and immediately respond to pathogens or injuries once the mucosa barriers are destroyed during IBD. GPR174 is an essential regulator of immunity which widely expressed in most immune cells including DCs. However, the role of GPR174 in regulating the immune function of DC in colitis has not been investigated. Methods Dextran sodium sulfate (DSS) was orally administrated to establish the colitis model. Data of weight, length of colon, disease activity index (DAI) and macroscopic scores were collected. Mean fluorescence intensity (MFI) of CD80, CD86, CD40, major histocompatibility complex-II (MHC-II), and T cells labelled with carboxifluorescein diacetate succinimidyl ester (CFSE), infiltrations of T cells, and DCs were detected by flow cytometry. The expression of cytokines (tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-10 (IL-10), interferon-γ (IFN-γ), interleukin -4 (IL-4)) and GPR174 mRNA were measured by Elisa, quantitative polymerase chain reaction (qPCR), and immunofluorescence. RNA of BMDCs was extracted for sequencing. Adoptive transfer of BMDCs was administrated intravenously. Results Gpr174-/- mice exposed to 3% DSS showed significant alleviation characterized by reduced loss of weight, more minor colon damage, and better DAI and macroscopic scores. The expression of pro-inflammatory cytokines (TNF-α, IL-6) decreased, while anti-inflammatory cytokine (IL-10) increased compared with WT mice. In vitro, Gpr174-/- BMDCs showed less maturity, with a declined expression of MHC-II, CD80, CD86 and reduced TNF-α, higher IL-10 after LPS stimulation. Gpr174-/- BMDCs were less capable of activating OT-II naïve CD4+ T cells than WT BMDCs, and induced more Th0 cells to differentiate into Treg while less into Th1. Furthermore, the transcriptome sequencing analysis exhibited that Gpr174 participated in TNF-α (NF-κB) signaling, leukocyte transendothelial migration, and Th1/Th2 cell differentiation pathways. Adoptive transfer of Gpr174-/- BMDCs to WT mice ameliorated DSS-induced colitis. Conclusion Our study indicated that Gpr174 was involved in the pathogenesis of IBD by regulating the maturation of the dendritic cells to maintain immune homeostasis. TNF-α (NF-κB) signaling pathway, leukocyte transendothelial migration, and Th1/Th2 cell differentiation pathways may be involved.